1998
DOI: 10.1021/ja973240w
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Nuclear Relaxation in an A2Spin System Initially Polarized through Para-Hydrogen

Abstract: Os 3 (CO) 10 (NCCH 3 ) 2 has been hydrogenated with para-hydrogen to yield H 2 Os 3 (CO) 10 where the two hydrogen nuclei remain magnetically equivalent and therefore in a singlet state. Despite this equivalence, an enhanced longitudinal magnetization is observed to decrease toward thermal equilibrium. It is postulated that this enhanced magnetization is created through a nuclear relaxation interference mechanism (cross-correlation between dipolar interaction and chemical shift anisotropy); decay curves are th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 18 publications
4
75
1
Order By: Relevance
“…The formation of hyperpolarized longitudinal magnetization derived from parahydrogen on magnetically equivalent protons was already observed 11 and it was demonstrated to be dependent on the intensity of the magnetic field at which the hydrogenation reaction takes place. In that case nuclear relaxation interference mechanism due to cross-correlation between dipolar interaction and chemical shift anisotropy was the reason for the observed hyperpolarized longitudinal magnetization derived from parahydrogen spin order on the A 2 spin system.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The formation of hyperpolarized longitudinal magnetization derived from parahydrogen on magnetically equivalent protons was already observed 11 and it was demonstrated to be dependent on the intensity of the magnetic field at which the hydrogenation reaction takes place. In that case nuclear relaxation interference mechanism due to cross-correlation between dipolar interaction and chemical shift anisotropy was the reason for the observed hyperpolarized longitudinal magnetization derived from parahydrogen spin order on the A 2 spin system.…”
Section: Resultsmentioning
confidence: 85%
“…Symmetrical substrates have already been shown to yield 1 H polarized patterns due to reaction intermediates 11 or to long range coupling with other protons of the product. 12 DFT optimization of the reaction intermediates and transition states are carried out in order to obtain mechanistic support to the experimentally observed PHIP effects and, in turn, to elucidate the occurring hydrogenation pathway.…”
Section: Introductionmentioning
confidence: 99%
“…In such circumstances, the Hamiltonian is reduced to the J-coupling part and may thus induce more transfers as explained in recent publications (28 -30). Nevertheless, as soon as the sample is placed in the strong magnetic field of the NMR spectrometer, the quantities that will survive are of the longitudinal spin-order type, unless this longitudinal spin order is transformed into magnetization by relaxation processes (20,31). This aspect is beyond the scope of this article.…”
Section: The Steady-state Density Operatormentioning
confidence: 97%
“…This differential enhancement was interpreted in terms of kinetic selectivity, demonstrating that the activation barrier for H 2 addition over the S-Ir-CO axis is significantly lower than that for H 2 addition over the S-Ir-P axis. Aime et al studied the addition of hydrogen to a tri-osmium cluster species, Os 3 (CO) 10 (NCCH 3 ) 2 , using PHIP methods [49]. The authors observed that the cluster reacted with parahydrogen, yielding an unexpectedly enhanced resonance for the chemically and magnetically equivalent bridging hydride ligands of the product Os 3 (CO) 10 (H) 2 .…”
Section: The Detection and Investigation Of Metal Hydride Speciesmentioning
confidence: 99%